Education is more culture project: interdisciplinarity in favor of the (re) construction of the cultural identity of the Traipu munifipality, Brazil/Projeto educação é mais cultura: a interdisciplinaridade em favor da (re)construção da identidade cultural traipuense - Cristina Simone de Sena Teixeira; Cristiano Cezar Gomes da Silva; Conceição Maria Dias de Lima (Universidade Estadual de Alagoas, 2020)
This article deals with the analysis of an interdisciplinary project entitled "Education is + Culture", developed in the schools of the Traipu Municipal Public School, Alagoas. The purpose is to highlight its contribution to the (re) construction of the traipuense cultural identity. The aim is also to provoke the reflection of education professionals about the importance of collaborative teaching practice in dealing with cross-cutting themes that, like the project, encourage the visualization, respect, appreciation and new interpretations of culture and identity. To this end, we adopted a bibliographic methodology and a qualitative approach based on theories of authors such as Bhabha (2007), Fazenda (2011), Freire (1987), Moreira and Candau (2008), Geertz (2001) and Hall (2006), besides being based on the BNCC (2017).